Deteksi Keberadaan Mikroba Indikator Dalam Es Kelapa Muda (Cocos Nucifera) Di Kecamatan Ujung Batu Kabupaten Rokan Hulu - Rio Andri; Al Muzafri; Lufita Nur Alfiah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Coconut ice is a food product that isconsidered safe for consumption, young coconut iceis made from young coconut mixed with ice crystalsand served in the form of a drink. Even though it isserved in a clean place to avoid the presence ofmicroorganisms, young coconut ice still has thepossibility of microorganisms containing microbialcontamination. This study aims to detect the presenceof Coliform in young coconut ice (Cocos nucifera),from various drinks sold in Ujung Batu District,Rokan Hulu Regency. The research method used isRandom Sampling, has been carried out fromSeptember to November 2021. The MPN (MostProbable Number) method is used to calculateColiform. A total of 8 samples were used in thisstudy. Observations showed that all positive samplescontained Coliform. Factors that can be a source ofcontamination such as ice crystals, young coconuts,tools and hygiene practices by sellers need to beconsidered so that young coconut water ice is freefrom Coliform contamination. The population of thisresearch is young coconut ice, covering Ujung BatuSubdistrict in Pematang Tebih Village, Suka DamaiVillage, Ujung Batu Village and Ngaso Village. Thesampling technique was random sampling based onthe amount of coconut ice purchased from traders.The results of data analysis showed that youngcoconut ice had been contaminated by coliformbacteria. Laboratory examination 8 samplescontained coliform microbes, 6 samples (>1600), 1sample (1600) and 1 sample (150) of the totalsamples. According to the Minister of Health of theRepublic of IndonesiaNo.492/MENKES/PER/IV/2020 concerning therequirements for drinking water quality, it is statedthat the number of coliform bacteria and Escherichiacoli bacteria in drinking water is 0/100 ml of watersample.